TMOD-23. DYNAMIC PATTERNS OF GLIOBLASTOMA CLONAL EVOLUTION IN RESPONSE TO CHEMORADIOTHERAPY. (5th November 2018) - Qazi, Maleeha; Venugopal, Chitra; Vora, Parvez; Nixon, Allison; Desmond, Kimberly; Singh, Mohini; Neil, Savage; Subapanditha, Minomi; Tong, Amy; Bakhshinyan, David; Mak, Annie; Yelle, Nicholas; et al.
Abstract: Despite aggressive multimodal therapy, glioblastoma (GBM) remains incurable and inevitably relapses. Recent data have implicated intratumoral heterogeneity as the driver of therapy resistance and tumour relapse in GBM. Models that capture the evolution of GBM biology in response to standard-of-care (SoC) chemoradiotherapy will allow for the identification of cellular mechanisms that govern GBM therapy failure. In this study, we coupled cellular DNA barcoding technology with our novel patient-derived xenograft SoC model (combined temozolomide and radiation treatment) to profile the clonal evolution of GBM stem cells (GSCs) through therapy. We report the successful barcoding of patient-derived primary, treatment-naive GSCs at a single cell resolution that were expanded into clonal populations, intracranially engrafted in immune-deficient mice, and treated with SoC therapy. We performed MRI imaging to identify spatial recurrence patterns of GSCs through the in vivo chemoradiotherapy model. We then interrogated the temporal fate of clonal barcoded GSC populations through SoC therapy model to identify differential barcode selection in response to treatment. Through this, we determined dynamics patterns of a pre-existing or a therapy-driven GSC subpopulation(s) seeding GBM tumour relapse. Profiling the dynamic nature of heterogeneous GBM subpopulations through disease progression and SoC treatment may lead to the identification of the modes of therapy resistance utilized by GBM to drive disease relapse.